A series of bowl-shaped PDI dimers designed for organic photovoltaic cells through engineering N-annulated bridge towards potential alternatives of PDI bridged dimer acceptors. (January 2018) - Yin, Hang; Sui, Ming-Yue; Pan, Qing-Qing; Sun, Guang-Yan; Geng, Yun
Abstract: Perylene diimides (PDIs ) dimer-based non-fullerene acceptors have made significant progress in the field of organic photovoltaics (OPVs) recently. To further renderPDI derivatives soluble and tailor self-assembly, the incorporation of N-annulations inPDI dimers becomes an effective strategy in latest researches. Here, we focus on engineeringPDI dimers with N-annulated bridges to construct bowl-shapedPDI dimers with the aim of improving efficiency, stereoscopic dimensions and the electron transfer abilities by introducing different functional linkers in N-annulated bridges. Besides some properties relevant to photovoltaic performance of these investigated acceptors were characterized based on density functional theory (DFT) and (time dependent density functional theory) TD-DFT calculations, Marcus semi-classical model was also employed to further estimate the exciton dissociation ability at D/A interface. Our results demonstrate that, compared to planar N-annulatedPDI dimers, bowl-shapedPDI dimers possess higher LUMO energy levels, larger open circuit voltage ( V OC ), complementary optical absorption with the donorPBDTTT-C-T, and more effective charge separation at the interface. Moreover, we highlight that introducingSF andNDT linkers in N-annulated bridges would be more favorable to optical performance. We expect that these modified N-annulatedPDI dimers could become potential acceptor materials in OPVs. Graphical abstract: Based on the configuration of planar N-annulatedPDI dimers, It would be a novel approach to improve the exciton dissociation efficiency that engineeringPDI dimers with N-annulated bridges constructing linked bowl shapes. For facilitating more effective efficiency, the aromatic linkers based on N-annulated bridges (π-bridge and D-bridge) were introduced between twoPDI based units. Here, D/4 andD/6 exhibit the most excellent optical performance, due to the introduction of expanded conjugated stereoscopic π-bridgeSF based on the symmetric bowl shape or the prospective "A-D-A" structure with D-bridgeNDT . Highlights: Introducing N-annulation at bay position of PDI dimers may construct bowl-shaped PDI dimers. Compared with planar dimers, bowl-shaped PDI dimers possess extended conjugated backbone, flexible electronic structures, complimentary optical absorption with donor and excellent charge transport performance. As for PBDTTT-C-T/PDI interface, installed SF and NDT linkers based on N-annulated bridges in PDI dimers exhibit more favorable performance.